Business professionals' perspectives of college students' volunteer experiences - Rogers, Brianne S. (My University, 2011)
Volunteer centers across the country could be at risk for losing funding as universities' budgets decline due to American's Great Recession. This decrease of funding is a greater risk for volunteer centers because of the lack of evidence of support that the centers contribute to the career preparation of college students. Through convenient and referral sampling methods data was collected from business professionals, and a significant difference was found in the type of skills business professionals perceive college students develop through volunteer experiences. Also, the value contributed to volunteer experiences during the hiring process compared to other college students' attributes was significantly less. Additionally, data was collected to provide descriptive statistics and general information about business professionals' perceptions of college students' volunteer experiences. The data analysis suggests that although business professionals see merit in college students volunteering, they do not equate volunteer experiences to college students' employability. Based on the research gathered, recommendations were given on how to motivate students, changes that could be made to volunteer centers' services, and the need to education business professionals about college students' volunteer experiences.
Keywords: Professional employees - Perceptions - United States.; Volunteers - United States.; Voluntarism.